Performance analysis of supercapacitors for transportation industry - Nagarajah V.J.; Lee H.J.; Tan K.G.; Khunprasit N. (Institute of Advanced Engineering and Science, 2023)
Monitoring device is essential to ensure a reliable and a healthy lifespan of the energy storage system. Hence, a monitoring device is needed to monitor the state of health and state of charge of a Supercapacitor. This project aims to demonstrate a method to monitor Supercapacitors using a microcontroller in both hardware and software approaches. The data was successfully collected by an online platform called ThingSpeak. 2019 Institute of Advanced Engineering and Science.